No wire? No problem: Resuscitative endovascular balloon occlusion of the aorta can be performed effectively and more rapidly with a wire-free device. Issue 5 (November 2018) - Romagnoli, Anna Noel; Teeter, William; Wasicek, Philip; Gamble, William Bryan; Hu, Peter; Stein, Deborah; Scalea, Thomas; Brenner, Megan
Abstract : BACKGROUND: A wire-free device is available for resuscitative endovascular balloon occlusion of the aorta (REBOA) providing aortic occlusion (AO) without lengthy platform guide-wires and large sheaths. METHODS: This was a retrospective, single-institution review of patients who received REBOA from May 2014 to September 2017. Timing of procedural steps was measured in seconds using time-stamped videography. RESULTS: Seventy-four patients received REBOA: 29 with a platform guidewire, 12-Fr sheath, and balloon catheter (W group), and 45 with a 7-Fr sheath and wire-free device (WF group). Mean age ( p = 0.22) and ISS ( p = 0.80) were similar between groups. Fifty-nine patients received REBOA at Zone 1, 15 patients at Zone 3. There was no difference in median [interquartile range] time to common femoral artery (CFA) access between the WF (194 [98–313] seconds) and W (193 [126–280] seconds) groups ( p = 0.96). Both median time to AO after CFA access (WF, 158 [109–264] seconds vs. W, 307 [222–390] seconds, p < 0.001) and median total procedural time (WF, 366 [263–596] seconds vs. W, 511 [441–597] seconds; p = 0.012) were significantly shorter with the wire-free system. The rates of percutaneous versus open CFA access was not different between groups ( p = 0.48). Both groups had a similar physiologic response to AO as measured by pre- and post-AO SBP ( p = 0.86). Overall mortality rate was 74%, 90% in the W group, and 64% in the WF group ( p = 0.027). The procedure-related complication rate was not significantly different between groups with regard to compartment syndrome (W, 3% vs. WF, 4%, p = 1.0), access-related complications (W, 0 vs. WF, 6%, p = 0.28), or systemic complication (W, 0 vs. WF, 9%, p = 0.15). CONCLUSION: Once CFA access is obtained, AO with a smaller wire-free device reduces procedural time by approximately 50%. When perfusion to proximal organs is essential, the seconds saved to achieve AO may contribute to improved mortality. Time to obtain CFA access is not dependent on introducer sheath size. LEVEL OF EVIDENCE: Therapeutic, level V.